Reply to Myszkowski et al. (2020): Some matters of fact concerning aesthetic sensitivity. (27th February 2020) - Nadal, Marcos; Corradi, Guido; Barrada, Juan Ramón; Clemente, Ana; Chuquichambi, Erick G.
Abstract : We respond to some of Myszkowski and colleagues' (2020, Br. J. Psychology ) critical comments on our recent work on aesthetic sensitivity (Corradi, Chuquichambi, Barrada, Clemente, & Nadal, 2020, Br. J. Psychology ). We show that these comments stem mostly from factual inaccuracies.